EFEKTIVITAS PENERAPAN SISTEM INSENTIF BAGI MANAJER DAN KARYAWAN - Dhiona Ayu Nani; Cinthia Annisa Vinahapsari (Institut Informatika Dan Bisnis (IIB) Darmajaya, 2020)
Incentives are awards given to managers or employees in order to motivate managers and employees to improve their performance, so that the company’s goal namely maximize shareholder value can be obtained. Shareholder value can be maximized through increased income. Increased income will cause an increase in stock prices, so that shareholder value will also increase. However, incentives can actually trigger deviant behavior for managers. The presence of the incentive system in the form of bonuses obtained by managers when managers can increase company profits, resulting in profit manipulation is inevitable. The company's profit which is manipulated so that it looks high for the personal benefit of the manager, will cause the company to suffer losses. On the other hand, incentives can create knowledge sharing between employees. This will further improve employee performance. Good employee performance will provide benefits for managers in achieving company goals that is maximizing shareholder value. This research is a qualitative research with literature review approach.Keywords — Incentives, Shareholder Value, Income, Knowledge Sharing